2015
DOI: 10.1634/theoncologist.2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Chemotherapy-Induced Ovarian Failure in Young Breast Cancer Patients: The Role of Vascular Toxicity

Abstract: Background. We previously reported that chemotherapy-induced ovarian toxicity may result from acute vascular insult, demonstrated by decreased ovarian blood flow and diminished posttreatment anti-Müllerian hormone (AMH) levels. In the present study, we report the continuous prospective evaluation of ovarian function in that cohort. Methods. Patients (aged,43 years) with localizedbreastcancer were evaluated by transvaginal ultrasound prior to initiation of chemotherapy, immediately at treatment completion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
6
28
0
Order By: Relevance
“…These authors also found that age was the most important risk factor for the occurrence of chemotherapy-induced amenorrhoea because the rate of amenorrhoea increased with increasing age. This finding was further corroborated by the work of Ben-Aharon et al [22], which showed that women under 35 years of age recovered from alterations in chemotherapy-induced ovarian circulation faster than their older counterparts. Menstrual disorders are likely to occur in women who already have some degree of aging ovarian function [23] [24].…”
Section: Discussionsupporting
confidence: 61%
“…These authors also found that age was the most important risk factor for the occurrence of chemotherapy-induced amenorrhoea because the rate of amenorrhoea increased with increasing age. This finding was further corroborated by the work of Ben-Aharon et al [22], which showed that women under 35 years of age recovered from alterations in chemotherapy-induced ovarian circulation faster than their older counterparts. Menstrual disorders are likely to occur in women who already have some degree of aging ovarian function [23] [24].…”
Section: Discussionsupporting
confidence: 61%
“…Experiments in rats showed that GnRHa inhibited estrogen-induced increase of ovarian perfusion and endothelial vessel area [20]. In humans, some studies reported a significant reduction in ovarian artery blood flow after short-and long-term administration of GnRHa [21,22], but others did not confirm these findings [23,24]. Although reducing the exposure to chemotherapy could have a protective effect on follicular pool, decreasing ovarian perfusion may also have a detrimental effect on chemotherapy-induced ovarian fibrosis.…”
Section: Indirect Effectmentioning
confidence: 99%
“…Long-term anxiety could cause dysfunction of the hypothalamic-pituitary-ovarian axis (HPOA), which can lead to DOR or premature ovarian failure (Nicoloro-SantaBarbara et al, 2017). Among these factors, alkylating chemotherapy agents, such as cyclophosphamide (CTX), which is highly gonad-toxic, led to a decrease in ovarian function and in anti-Müllerian hormone (AMH) (Ben-Aharon et al, 2015). It could induce ovarian damage by activation of the PI3K/AKT and mTOR pathways (Goldman et al, 2017), leading to primordial follicle activation and follicular "burnout" (Chang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%